Virtual Therapy with the NMDA Antagonist Memantine in Hippocampal Models of Moderate to Severe Alzheimer's Disease, in Silico Trials - Dariusz Świetlik; Jacek Białowąs; Aida Kusiak; Marta Krasny (MDPI AG, 2022)
The variability in clinical trial results on memantine treatment of Alzheimer's disease remains incompletely explained. The aim of this in silico study is a virtual memantine therapy for Alzheimer's disease that provides a different perspective on clinical trials; An in silico randomised trial using virtual hippocampi to treat moderate to severe Alzheimer's disease with doses of memantine 3-30 µM compared to placebo. The primary endpoint was the number of impulses (spikes). Secondary endpoints included interspike interval and frequency; The number of virtual moderate-AD hippocampal spikes was significantly lower, at 1648.7 (95% CI, 1344.5-1952.9), versus those treated with the 3 µM dose, 2324.7 (95% CI, 2045.9-2603.5), and the 10 µM dose, 3607.0 (95% CI, 3137.6-4076.4). In contrast, the number of virtual spikes (spikes) of severe AD of the hippocampus was significantly lower, at 1461.8 (95% CI, 1196.2-1727.4), versus those treated with the 10 µM dose, at 2734.5 (95% CI, 2369.8-3099.2), and the 30 µM dose, at 3748.9 (95% CI, 3219.8-4278.0). The results of the analysis of secondary endpoints, interspike intervals and frequencies changed statistically significantly relative to the placebo; The results of the in silico study confirm that memantine monotherapy is effective in the treatment of moderate to severe Alzheimer's disease, as assessed by various neuronal parameters.